An American renaissance in the year 2000: 74 trends that will effect America's future—and yours. - Cetron, Marvin (Futurist)
An excerpt from the forthcoming second edition of American Renaissance enumerates 74 trends and forecasts for the United States of the year 2000 in the categories of society, technology, education, labor, management, values, the family, and institutions. Based on these trends, the author expects the country to experience a rebirth in coming years. He says that his findings make him very optimistic.